2011
DOI: 10.1016/j.foreco.2010.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Semi-forest coffee cultivation and the conservation of Ethiopian Afromontane rainforest fragments

Abstract: a b s t r a c tCoffea arabica shrubs are indigenous to the understorey of the moist evergreen montane rainforest of Ethiopia. Semi-forest coffee is harvested from semi-wild plants in forest fragments where farmers thin the upper canopy and annually slash the undergrowth. This traditional method of coffee cultivation is a driver for preservation of indigenous forest cover, differing from other forms of agriculture and land use which tend to reduce forest cover. Because coffee farmers are primarily interested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 41 publications
11
114
2
Order By: Relevance
“…Higher Available Potassium (4.98) was from C. africana (Table 2). Inline of the current study the earlier finding of Aerts et al (2011) from south west Ethiopia shown higher pH, per cent N and Carbon from M. ferruginea; higher Cation exchange capacity and potassium from C. macrostachyus; higher Phosphorus from and A. gummifera, respectively.…”
Section: Soil Factors Affecting Coffee Productionsupporting
confidence: 72%
See 3 more Smart Citations
“…Higher Available Potassium (4.98) was from C. africana (Table 2). Inline of the current study the earlier finding of Aerts et al (2011) from south west Ethiopia shown higher pH, per cent N and Carbon from M. ferruginea; higher Cation exchange capacity and potassium from C. macrostachyus; higher Phosphorus from and A. gummifera, respectively.…”
Section: Soil Factors Affecting Coffee Productionsupporting
confidence: 72%
“…However, higher coffee weight (237.99 g/1000 bean) and bean yield (3.09 Mg ha -1 ) were observed under C. macrostachyus (Table 2). Similarly, earlier studies also confirm the relative higher yield under Millettia ferruginea (Aerts et al, 2011) and significantly highest under A. abyssinica (Kufa et al, 2007). Such variation may caused from soil organic matter, total nitrogen and organic carbon provided by the plants (Kufa et al, 2007;Aerts et al, 2011).…”
Section: Coffee Weightsupporting
confidence: 66%
See 2 more Smart Citations
“…S1-S4) and local people rely on these church forests for the provisioning of livestock feed, tree seedlings, fuelwood, honey, clean water and other essential ecosystem services including shade, climate regulation, habitat for pollinators and spiritual values (Cardelús et al 2012;Amare et al 2016). In the southwest of the country, shade coffee cultivation has, until now, guaranteed that more or less natural forest remained an important land cover (Tadesse et al 2014), despite the clear trade-off between coffee productivity and forest ecological quality (Senbeta and Denich 2006;Schmitt et al 2010;Aerts et al 2011;Hundera et al 2013). In the central and northern Ethiopian highlands, however, high historical land use pressure has resulted in widespread deforestation and land degradation (Darbyshire et al 2003;Nyssen et al 2004).…”
Section: Introductionmentioning
confidence: 99%